Development of Tourism Logistics Management of Tha Chalom, Samut Sakhon Province - Bunjongkanit, Sarunthorn; Laoketkarn, Chatchai (Journal of Humanities and Social Sciences Thonburi University, 2024)
This research aims to 1) study the perception of tourism elements and the potential of tourism logistics management of Tha Chalom Subdistrict Samut Sakhon province and 2) study guidelines for developing tourism logistics management in Tha Chalom Subdistrict, Samut Sakhon province. research operations is a mixed methods research, which is quantitative research using questionnaires as a tool for collecting data. The population and sample group were 392 tourists who visited Tha Chalom subdistrict and qualitative research using in-depth interviews including interviews with store operators, social enterprise group and government officials. Results of the level of awareness of the components of tourist attractions in Tha Chalom subdistrict, Samut Sakhon province has a value equal to 4.11, at high level. In terms of analyzing the tourism logistics management potential of Tha Chalom Subdistrict, it was found that it was ready in terms of both physical flow, information flow, and financial flow. The results from studying the guidelines for developing tourism logistics management in Tha Chalom Subdistrict are ready in various aspects. Able to support tourists in every dimension. There should be tourist routes maps and signposts. A joint agency between the government, private sector and local government should be established to develop tourist attractions in Tha Chalom Subdistrict area. Samut Sakhon Province efficiently These actions will help tourism in the Tha Chalom Subdistrict area continue to grow and grow sustainably.